Assesment of radiotherapy effects on the blood flow in gingiva and dental pulp : a laser Doppler flowmetry study (Journal of Applied Oral Science, 2022)
Objective: This study aims to determine and compare the dental pulp and gingival blood flow in patients referred for oropharyngeal radiotherapy (RT) at three different time points: before the start, immediately after, and six months following the completion of RT. The aim is also to evaluate the dependence of the pulp and gingival blood flow on the radiation dose. Methodology: A prospective study included 10 patients referred for intensity-modulated RT (IMRT) in the oropharyngeal region, with at least one intact tooth surrounded by a healthy gingiva. The dose received by each selected tooth and adjacent gingiva was determined according to the map of treatment planning and computer systems. The blood flow measurements were performed using the laser Doppler flowmetry (LDF) method. Results: Comparing vascular flows at three different time points, the median blood flow in the dental pulp showed no statistically significant difference (p=0.325), contrary to gingiva (p=0.011). Immediately after RT completion, the gingival flow significantly increased compared to its starting point (p=0.012). The pulp flow correlated negatively with the radiation dose, whereas a strong correlation was noted 6 months following the RT completion. Conclusions: RT caused a significant acute gingival blood flow increase, followed by a long-term (over six months) tendency to return to the starting levels. The dental pulp blood flow is differently affected by higher radiation doses (over 50Gy) in comparison to lower doses (below 50Gy). During RT planning, considering the possibility of protecting the teeth localized near the Gross Tumor Volume as a sensitive organ is recommended.